Transtensional tectonics during the Gondwana breakup in northeastern Brazil: Early Cretaceous paleostress inversion in the Araripe Basin - Rosa, Milena Cristina [UNESP] (2023)
Intraplate deformation during the Mesozoic breakup of West Gondwana predominantly occurred along major ancient lithospheric discontinuities. The Precambrian Patos Shear Zone (PASZ) is an inherited lithospheric discontinuity in the interior of northeastern Brazil which is closely linked to the evolution of the Araripe Basin. In this study, unlike previous interpretations of purely extensional tectonics, we conducted stratigraphic and structural field mapping as well as paleostress reconstruction to demonstrate the role of intraplate transtensional tectonics during the Araripe Basin evolution. Limited to the north by the PASZ and associated with sinistral reactivation, a set of normal to oblique NE–SW faults constituting a transtensional horsetail structure generated the initial basin geometry. Stratigraphic records of this rift phase comprise the Jurassic to Early Cretaceous Brejo Santo, Missão Velha, and Abaiara formations. Paleostress reconstruction showed a NE–SW/subhorizontal σ1 axis, a vertical σ2 axis, and a NW–SE/subhorizontal σ3 axis, resulting in a sinistral transtensional tectonic regime, which was mainly governed by intraplate processes that reflected the opening of the Brazilian East Margin. The subsequent Aptian post-rift early phase was characterized by NE–SW reverse faults and a succession of normal to oblique normal faults striking NW–SE to WNW–ESE. This fault arrangement generated a new NW–SE transtensional basin, which controlled the Barbalha Formation and modified and partially preserved the previous NE-SW transtensional basin. Paleostress reconstruction showed a NW–SE/subhorizontal σ1 axis and NE–SW/subhorizontal σ3 axis for strike-slip faults but NE–SW extension for normal faults. This is related to a second dextral reactivation of the PASZ following propagation of intraplate stress during the opening of the Brazilian Equatorial Margin. In summary, tectonic evolution of the Araripe Basin was strongly influenced by stress propagation from the Gondwana breakup into intraplate settings, with two distinct reactivations of the PASZ pre-existing basement structures which results in a paleostress inversion during basin evolution.